APPLICATION OF NEW ALTERNATIVE MODELS OF FINITE ELEMENT METHOD IN PROBLEMS OF ROD TORSION (Academic journal Industrial Machine Building Civil Engineering, 2017)
The work is dedicated to the problem solution of prismatic bars torsion with a rectangular section by the finite element method with the use of standard and alternative serendipian models. By the solving of the inverse problem considering the precise value for maximum shear stress, the new improved models on the biquadratic and bicubic serendipian elements were received. By using new alternative models as well as standard models, the shear stresses in two dangerous points of section and the torque for different ratio of the rectangle’s sides were defined. The obtained results allow to solve various application problems of physical fields restoring occuedr in technical systems and objects by developing new mathematical models.
Keywords: prismatic rod; stress function; torque; shear stresses; finite element; basic function